2001
DOI: 10.1002/1097-0010(20010101)81:1<88::aid-jsfa787>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1, zearalenone and deoxynivalenol production by Fusarium moniliforme, F proliferatum and F graminearum in mixed cultures on irradiated maize kernels

Abstract: The impact on fungal growth and mycotoxin formation of interactions between fumonisinproducing isolates of Fusarium moniliforme and F proliferatum and a zearalenone (ZEA)-and deoxynivalenol (DON)-producing isolate of F graminearum inoculated together on irradiated maize at 15 and 25°C and at 0.98, 0.95 and 0.93 a w was studied. The presence of F graminearum decreased the fungal populations (CFU g À1 grain) of F moniliforme and F proliferatum under almost all conditions tested. In the presence of F moniliforme,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
2
11
2
1
Order By: Relevance
“…In contrast to our observations, stimulation of F. graminearum DON production was reported in the competition with Fusarium verticillium or Fusarium proliferatum on irradiated maize kernels (Velluti et al , 2001). Fungal biomasses were not quantified in this study, and it is possible that higher DON levels resulted from a stimulated F. graminearum growth.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our observations, stimulation of F. graminearum DON production was reported in the competition with Fusarium verticillium or Fusarium proliferatum on irradiated maize kernels (Velluti et al , 2001). Fungal biomasses were not quantified in this study, and it is possible that higher DON levels resulted from a stimulated F. graminearum growth.…”
Section: Resultscontrasting
confidence: 99%
“…We used our PCR assays to test the competitive ability of a DON-producing F. graminearum and its nontoxigenic mutant against the biocontrol candidate T. atroviride in a standardized microcosm with autoclaved maize leaf tissue. As we found no evidence for a recently suggested competitive advantage conferred by F. graminearum DON production (Velluti et al, 2001;Lutz et al, 2003), biocontrol application of Trichoderma is unlikely to increase selection for toxigenic F. graminearum specimens; this needs to be proven under field conditions. In our competition assays, we further observed partially reduced DON production per F. graminearum wild-type biomass in the presence of T. atroviride.…”
Section: Role Of Fusarium Graminearum Don Production In the Interacticontrasting
confidence: 79%
“…(2000a) noted that the growth rate of F. graminearum was relatively unaffected by the presence of competing species, whereas the growth of F. proliferatum and F. moniliforme was reduced. However, a similar study by the same authors (Velluti et al ., 2000b) found that mixed culture of F. graminearum with either F. proliferatum or F. moniliforme led to a larger total fungal population than occurred with the growth of F. graminearum alone. Their study quantified the total population by colony counts only, without quantifying each species individually.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have indicated that the growth and toxin production of toxigenic Fusarium species can be affected by the presence of competing fungi (Ramakrishna et al ., 1996; Velluti et al ., 2000a) and that toxin production can, in some circumstances, be stimulated in these interactions. Much of the work in this area has relied on the isolation and enumeration of colony‐forming units to quantify the mixed population (Ramakrishna et al ., 1996), sometimes without specific quantification of each pathogen (Velluti et al ., 2000a,b). Molecular assays to detect and individually quantify the major pathogens involved in the Fusarium ear blight and stem base disease complexes have now been developed (Nicholson et al ., 1996; 1998), and these assays are used here to investigate the nature of interactions between some components of the disease complexes.…”
Section: Introductionmentioning
confidence: 99%
“…, 1999) in maize ears whereas in vitro studies yielded opposite results (Marín et al. , 1998; Velluti et al. , 2000, 2001).…”
Section: Introductionmentioning
confidence: 94%